Disynaptic Subthalamic Input to the Posterior Cerebellum in Rat - Jwair, Saad; Coulon, Patrice; Ruigrok, Tom J. H. (Frontiers in Neuroanatomy, 2017)
In the last decade, the interplay between basal ganglia and cerebellar functions has been increasingly advocated to explain their joint operation in both normal and pathological conditions. Yet, insight into the neuroanatomical basis of this interplay between both subcortical structures remains sparse and is mainly derived from work in primates. Here, in rodents, we have studied the existence of a potential disynaptic connection between the subthalamic nucleus (STN) and the cerebellar cortex as has been demonstrated earlier for the primate. A mixture of unmodified rabies virus (RABV: CVS 11) and cholera toxin B-subunit (CTb) was injected at places in the posterior cerebellar cortex of nine rats. The survival time was chosen to allow for disynaptic retrograde transneuronal infection of RABV. We examined the STN for neurons infected with RABV in all nine cases and related the results with the location of the RABV/CTb injection site, which ranged from the vermis of lobule VII, to the paravermis and hemispheres of the paramedian lobule and crus 2a. We found that cases with injection sites in the vermis of lobule VII showed prominent RABV labeling in the STN. In contrast, almost no subthalamic labeling was noted in cases with paravermal or hemispheral injection sites. We show circumstantial evidence that not only the pontine nuclei but also the pedunculotegmental nucleus may act as the intermediary in the connection from STN to cerebellar cortex. This finding implies that in the rat the STN links disynaptically to the vermal part of lobule VII of the cerebellar cortex, without any major involvement of the cerebellar areas that are linked to sensorimotor functions. As vermal lobule VII recently has been shown to process disynaptic input from the retrosplenial and orbitofrontal cortices, we hypothesize that in the rat the subthalamic input to cerebellar function might be used to influence more prominently non-motor functions of the cerebellum than motor functions. This latter aspect seems to contradict the primate results and could point to a more elaborate interaction between basal ganglia and cerebellum in more demanding motor tasks.